Anti-inflammatory constituents from Phyllostachys makinoi Hayata. Issue 6 (19th March 2022) - Liaw, Chia-Ching; Lin, Yu-Chi; Wu, Shao-Yu; Kuo, Jenny Chun-Ling; Lin, Zhi-Hu; Lin, Kai-Wei; Hui-Chi, Huang; Yang Kuo, Li-Ming; Kuo, Yao-Haur
Abstract: A novel chromone analogue, phyllomakin A (1 ), and a new flavonolignan, (-)-quiquelignan C (2 ), along with 18 phenolic and 2 triterpenoids, were isolated from the leaves of Phyllostachys makinoi Hayata. The structures of 1 –22 were elucidated by an application of various spectroscopic analyses (1D & 2D NMR and MS) and compared with reported data. A biological evaluation showed that compound 3 had very potent anti-NO production activity (IC50 = 4.80 µM), while compounds 2, 6, 11, and 15 showed moderate inhibitory effects (IC50 = 10.19, 13.26, 13.56, and 10.96 µM, respectively) without affecting cell viability at 20 μM. GRAPHICAL ABSTRACT: